The fourth year : building on the foundations: 1991-92 annual report - SCES/SFU Joint Steering Committee (Author); Secwepemc Cultural Education Society (Author); Simon Fraser University (Author) (Secwepemc Cultural Education Society, 1992)
This booklet represents the fourth annual report on the partnership program between Simon Fraser University and the Secwepemc Cultural Education Society, covering the 1991-92 Academic Year. As previously, it evaluates the progress of the university program for First Nations students in Kamloops throughout the Fall 1991, and the Spring and Summer semesters 1992, focusing on both the educational and research oriented activities of the program. Not peer reviewed Annual report SCES/SFU Program